Outpatient Service Provision In Tertiary Hospital During Covid-19 Pandemic (Journal of Preventive and Social Medicine, 2024)
Background: The COVID-19 pandemic was a challenge for healthcare professionals globally. The outpatient department is an important part of the hospital. Service providers were facing tremendous difficulties and challenges due to sudden thrust of the pandemic. Despite these challenges service providers had to give service during COVID-19 pandemic. The purpose of this study to assess the state of outpatient service in tertiary hospital during COVID-19 pandemic.Methods: This cross-sectional study was conducted among conveniently selected 203 service providers including 156 doctors and 47 nurses. Data were collected through face-to-face interview using semi-structured questionnaire and observation checklist. The study was conducted at medicine, surgery, paediatric and family planning outpatient department of Shaheed Suhrawardy Medical College Hospital, Dhaka Medical College Hospital, and Bangabandhu Sheikh Mujib Medical University during the period from January to December 2021.Results: Among 203 service providers, 76.8% were doctors and 23.2% were nurses. All health services were available during COVID-19 pandemic in outpatient departments (OPDs) of the selected hospitals. At outpatient department there was separate entry-exit door, thermal scan was available at entry point, Patients and visitors are restricted. Number of patients were decrease in outpatient department. Among the three hospitals facility of flu-corner and triage in the OPD of ShSMCH. For the DMCH and BSMMU, flu-corner and triage center were situated at other premises of the hospitals. Outdoor surgery, vaccination service and shishu bikash kendro were open during COVID-19 pandemic. About 80.8% respondents mentioned about availability of adequate amount of personal protective equipment, 42.9% respondents mentioned about proper ventilation, 57.1% respondents said had not. About 32.5% respondent said about availability of N-95 mask and 57.6% said had not. Among the respondents 67.0% said they maintained physical distance during consult with the patients. 57.6% respondents said about lack of manpower. 61.6% respondents said about felt anxiety and high-risk during service.Conclusion: For more improvement of outpatient service during COVID-19 pandemic, the authority should pay special attention, to increase manpower, arrange frequent training for service providers.JOPSOM 2021; 41(2):20-27